Presentation and resolution of gender dysphoria as a positive symptom in a young schizophrenic man who presented with self‐emasculation: Frontiers of bioethics, psychiatry, and microsurgical genital reconstruction. Issue 9 (28th July 2020) - Wilcox Vanden Berg, Rand N.; Gaffney, Christopher D.; Paduch, Darius A.
Abstract: Gender dysphoria can present as a positive symptom of schizophrenia. Completion of gender affirmation surgeries should not occur as a result of male genital self‐mutilation via a deferral of emergent surgical reconstruction. Instead, gender affirmation should be considered after a full workup and assessment for resolution of any acute psychosis. Abstract : Gender dysphoria can present as a positive symptom of schizophrenia. Completion of gender affirmation surgeries should not occur as a result of male genital self‐mutilation via a deferral of emergent surgical reconstruction. Instead, gender affirmation should be considered after a full workup and assessment for resolution of any acute psychosis.